Studiu privind evoluția procedurilor de atribuire a contractelor publice de achiziții din România în perioada 2021–2023 - Paul Vasile Zai; Gabriela Iosifaru (Revista Transilvană de Ştiinţe Administrative, 2024)
Public procurement is essential for the effective distribution of governmental resources, significantly influencing the quality of public services and infrastructure. However, the complexities and challenges inherent in public procurement often lead to inefficiencies and budget overruns. This research underscores the importance of analyzing historical procurement data to enhance budget planning and forecasting. This case study analyses public procurement in Romania between 2021-2023 and is using the most relevant databases in the field. Issues related to legislation, institutions, strategies, and implementation are mentioned. The total number of public contract awards increased from 29,324 in 2012 to 32,087 in 2022, but decreased slightly to 29,587 in 2023, influenced by economic, political or operational factors during each year. The total value of the award of public contracts increased from 160,412,962 lei in 2021 to 319,487,336 lei in 2022 and then to 668,708,359 lei in 2023. The public procurement contract was the most used method of award. By examining patterns, trends, and anomalies in past procurement activities, public entities can make more informed decisions, optimize resource allocation, and reduce the likelihood of financial discrepancies. Additionally, the study highlights the critical role of a well-structured public procurement process, emphasizing how transparency, competition, and accountability contribute to better outcomes. Through a comprehensive analysis of historical data, this paper demonstrates how public procurement can be transformed into a more strategic tool for achieving economic efficiency and public value.